An extended TODIM method for project manager’s competency evaluation - Yin, Jielin; Guo, Jian; Ji, Tianmeng; Cai, Jingru; Xiao, Lei; Dong, Zhao (Journal of Civil Engineering and Management, 2019)
The project managers’ high efficiency and leadership ability is very important for the success of the whole project. Evaluating the competency of project manager accurately and selecting the suitable project manager from alternatives is a very core research issue that should be paid high attention to in the field of project management. When evaluating the competency of project manager, multiple criteria with interactive relationship should be considered, and the decision makers may have bounded rational behavior which may have a great impact on the result of evaluation, whereas the decision makes’ psychological behavior is rarely taken into account in the existing studies on the evaluation of project managers’ competency. TODIM (an acronym in Portuguese of interactive and multi-criteria decision making) is a multi-criteria decision making method considering the decision makers’ behavior. In this paper, an extended TODIM method which combines λ -fuzzy measure with Choquet integral considering incomplete criteria information and decision makers’ bounded rational behaviors are presented to evaluate the competency of project manager. Furthermore, a numerical example is presented to illustrate the method proposed. We hope that this method can provide some valuable references for the evaluation of project manager’s competency.